If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2x + 2 = -1 Reorder the terms: 2 + x + -2x = -1 Combine like terms: x + -2x = -1x 2 + -1x = -1 Solving 2 + -1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = -1 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -1 + -2 -1x = -1 + -2 Combine like terms: -1 + -2 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| w+5.3=-10.1 | | 14x+9=30-x | | 13j-100=7j-680 | | x^2+11=10x-5 | | .25(12-8x)=4(-2x-6) | | x-4+9=0 | | 15=4q+3 | | x^2-4x=-2x+63 | | -4.5+12.3=-23.7 | | 9(v-89)=27 | | x+2x-4=-13 | | 3+5c=-12 | | x+2x-4=13 | | 24=100 | | 11-11+3x=38-11 | | Y^3-8y^2-9y+72=0 | | x^2+150x-5000=0 | | -1.5x+6y=8 | | 5X-2(X+3)-1=9(2X-5) | | 9x-9=6x+6 | | -2x-29=-7(3x-4) | | x^2-10x+90=9 | | -27*-32= | | 19x-13=-103 | | 5x^3+10=40 | | 47*-16= | | 186x-y=10 | | x^3+7=-1 | | 7x^2-x-12= | | x^2-6x=8x+80 | | -14*92= | | 4x+4y+5z= |